Pattern, Etiology and Risk Factors for Tooth Extraction in Adult Population (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to determine pattern, causes and risk factors of dental extractions. Six hundred patients were included in this study.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at Bibi Aseefa Dental College Shaheed Mohtarma Benazir Bhutto Medical University Larkana from January 2012 to January 2013.Materials and Methods: A detailed clinical and radiological examination was carried out to determine the reasons of tooth extraction which were classified into a) caries, b) periodontal disease, c) orthodontic, d) prosthodontic, e) trauma, f) others such as endodontic procedure failure and fracture root. The data were processed and analyzed statistically to determine association of risk factors for tooth extraction by using Statistical Package for Social sciences (SPSS version 17).Results: Among 600 patients 412 were male, 188 were female. Tooth types were assessed which revealed, molars (Both upper and lower) 73%, Premolars 21% and Anteriors 6%. Causes of tooth extraction were analyzed which shows, Caries 57%,Periodontitis 27.8%, Endodontic treatment failure 6.8% and traumatic tooth failure 3.3%.While analyzing the association of cause of tooth extraction and socio-economic group, it is evident by statistically significant value of p=0.0035 that lower socio-economic has higher incidence of tooth extraction.Conclusion: This study shows that carries and periodontal disease are the principal causes for tooth extraction in the population of Larkana, Sindh. The majority of patients had incomplete secondary education or lower and had even more teeth extracted than patients having higher levels of education.